Do Bilinguals Acquire Similar Words to Monolinguals? An Examination of Word Acquisition and the Similarity Effect in Japanese-English Bilinguals' Vocabularies - Aya Kutsuki (MDPI AG, 2021)
Previous research has paid much attention to the overall acquisition of vocabularies among bilingual children in comparison to their monolingual counterparts. Much less attention has been paid to the type of words acquired and the possible transfer or cross-linguistic effects of the other language on vocabulary development. Thus, this study aims to explore similarities and dissimilarities in the vocabularies of simultaneous bilinguals and Japanese monolinguals and considers the possible cross-linguistic similarity effect on word acquisition. Six simultaneous Japanese-English bilingual children (mean age = 34.75 months (2.56)) were language-age-matched with six Japanese monolinguals; their productive vocabularies were compared regarding size and categories. Additionally, characteristic acquired words were compared using correspondence analyses. Results showed that, although delayed due to the reduced inputs, young bilinguals have a similar set of vocabularies in terms of word category as monolinguals. However, bilingual children's vocabularies reflect their unevenly distributed experience with the language. Fewer interactive experiences with language speakers may result in a lower acquisition of interactive words. Furthermore, there is a cross-linguistic effect on acquisition, likely caused by form similarity between Japanese katakana words and English words. Even between languages with great dissimilarities, resources and cues are sought and used to facilitate bilingual vocabulary acquisition.